Software defined intelligent satellite-terrestrial integrated wireless network - Shuo YUAN; Yijing REN; Zeyu WANG; Yaohua SUN; Mugen PENG (Dianxin kexue, 2021)
With the superiorities of providing network services for all scenarios of three-dimensional space, air, ground, and ocean, and satisfying the future network differential requirements on all services, the satellite-terrestrial integrated network (STIN) has become a hot spot in the development of 6G.Firstly, the current research development of the low-orbit satellite constellation and STIN were reviewed, and the challenges faced by the integrated satellite-terrestrial networking were discussed.Then, the software defined intelligent system architecture of the integrated satellite-terrestrial wireless network based on distributed SDN controllers was proposed to address the characteristics of STIN such as the complex architecture, high dynamic of network topology, the heterogeneity of network devices and protocols, which facilitated efficient satellite-terrestrial collaborative network management and control.In the end, the key techniques of the satellite-terrestrial flexible and reconfigurable collaborative networking were outlined, and the future development were presented.